(untitled) (Research, Society and Development, 2022)
Objective: to analyze the scientific evidence available in the literature regarding prenatal consultation performed by prenatal nurses from 2016 to 2021, based on the dimensions of the nurse’s work: care, educational, managerial and investigative. Method: integrative review in six stages in the databases: Scielo, Lilacs - MedLine, PubMed, BDENF. Results: Twenty-one articles were identified, organized into four categories: care dimension (8), managerial dimension (7), Educational dimension (4) and investigative dimension(2). Conclusions: in the care dimension, prenatal actions in relation to nursing consultation and health education guarantee the bond of the nurse and pregnant women and can contribute greatly to the outcome of pregnancy. A knowledge gap was evidenced in relation to the nurse’s investigative dimension. The low number of publications reveals the need to expand publications on the development of the systematization of nursing care in prenatal care and the importance of the role of nurses with managers of these services.